DERIVATION AND ANALYSIS OF MAXIMUM AND CONDITIONAL WORK OF AN ELECTROMAGNET IN RELAYS WITH SMALL GAPS AND CONSTANT ARMATURE LOAD - Chambega, D. J. (Tanzania Journal of Engineering and Technology, 2018)
Abstract